2020
DOI: 10.1007/s12311-020-01113-x
|View full text |Cite
|
Sign up to set email alerts
|

A Variation in FGF14 Is Associated with Downbeat Nystagmus in a Genome-Wide Association Study

Abstract: Downbeat nystagmus (DBN) is a frequent form of acquired persisting central fixation nystagmus, often associated with other cerebellar ocular signs, such as saccadic smooth pursuit or gaze-holding deficits. Despite its distinct clinical features, the underlying etiology of DBN often remains unclear. Therefore, a genome-wide association study (GWAS) was conducted in 106 patients and 2609 healthy controls of European ancestry to identify genetic variants associated with DBN. A genome-wide significant association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 64 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…Genetic testing for infantile nystagmus 27 and DBN 28 29 may improve diagnoses. Implementing home-based vestibular event monitoring by patient-initiated capture of ictal nystagmus could help in detecting nystagmus during vertiginous attacks and in the differential diagnosis of three of the most commonly encountered causes of episodic vertigo: vestibular migraine (VM), Meniere's disease, and benign paroxysmal positional vertigo (BPPV).…”
Section: General Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic testing for infantile nystagmus 27 and DBN 28 29 may improve diagnoses. Implementing home-based vestibular event monitoring by patient-initiated capture of ictal nystagmus could help in detecting nystagmus during vertiginous attacks and in the differential diagnosis of three of the most commonly encountered causes of episodic vertigo: vestibular migraine (VM), Meniere's disease, and benign paroxysmal positional vertigo (BPPV).…”
Section: General Findingsmentioning
confidence: 99%
“…FGF14 is expressed in Purkinje cells (PCs), and its reduction leads to decreases in the spontaneous firing rate and excitability of PCs, which are compatible with the pathophysiology of DBN. 29 In addition, mutations in the FGF14 gene cause episodic ataxia type 9 37 and spinocerebellar ataxia type 27 (SCA27). 28 FGF14-associated phenotypes also highlight the overlap between progressive and episodic ataxias, similar to those observed in mutations involving CACNA1A.…”
Section: Spontaneous Nystagmusmentioning
confidence: 99%
“…Despite numerous therapies, the success remains often unpredictable and incomplete. A recent study published in this volume of the Cerebellum has shed light towards better understanding of the "idiopathic" DBN [3]. A genome-wide association study of 106 patients of European ancestry identified genetic variants.…”
mentioning
confidence: 99%
“…A genome-wide association study of 106 patients of European ancestry identified genetic variants. One of the most common variants was on chromosome 13 located within the fibroblast growth factor 14 (FGF14) gene, a gene heavily expressed in the cerebellar Purkinje neurons, the sole output of the cerebellar cortex circuitry [3]. Reduction of the FGF14 is known to cause decreased spontaneous firing and excitability of the Purkinje neurons via its role in modulating voltagegated ion channels [4][5][6][7][8].…”
mentioning
confidence: 99%
See 1 more Smart Citation